Prevalence of congenital anomalies at birth among live births in the state of Maranhão from 2001 to 2016: temporal and spatial analysis - Luzivan Costa Reis; Márcia Helena Barbian; Augusto César Cardoso-; Elis Vanessa de Lima Silva; Juliano André Boquett; Lavínia Schuler-Faccini
ABSTRACT: Objectives: To analyze the prevalence at birth and the spatial and temporal distribution of congenital anomalies (CAs) among live births in the state of Maranhão in 2001 to 2016. To describe demographic, gestational and neonatal variables of interest. Methods: Ecological, population-based study, using secondary data from the Live Birth Information System (SINASC). Annual prevalence of total and per-group CAs was calculated. Spatial analyzes were based on the Local Indicators of Spatial Association (LISA) and the Moran I Index, and interactive maps were generated. Demographic, gestational and neonatal variables of interest available from SINASC were described in the group of newborns with CAs. Results: 1,831,830 live births, 6,110 with CAs (33.4/10,000) were included. Higher frequencies occurred in more recent years. Spatial clusters have been observed in specific years. The prevalence of newborns with CAs was different between categories of variables considered as risk factors for this outcome. Conclusion: The prevalence at birth of total CAs was lower than expected for major human defects (3%). The temporal peak of records in 2015/2016 is probably related to the increase in CAs caused by gestational infection by the Zika virus. The spatial clusters were probably due to variations at random due to the small number of births as they are not repeated in other years. Studies like this are the basis for the establishment of CA surveillance programs.